2022
DOI: 10.1021/acs.jpca.2c01773
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Electronic and Geometric Structure Tunes Organic Biradical Character in Bimetallic Tetrathiafulvalene Tetrathiolate Complexes

Abstract: The synthesis and design of organic biradicals with tunable singlet–triplet gaps have become the subject of significant research interest, owing to their possible photochemical applications and use in the development of molecular switches and conductors. Recently, tetrathiafulvalene tetrathiolate (TTFtt) has been demonstrated to exhibit such organic biradical character in doubly ionized bimetallic complexes. In this article we use high-level ab initio calculations to interrogate the electronic structure of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 85 publications
2
4
0
Order By: Relevance
“…To verify the accuracy of the percentage of diradical, we made a comparison with the results obtained from CASSCF (10,10) calculations (Table S4). From Table S4, we found that the trend given by the CASSCF method is consistent with our calculations under UM06-2X/6-311++G (d, p), which confirms the accuracy of the present work.…”
Section: Resultssupporting
confidence: 90%
“…To verify the accuracy of the percentage of diradical, we made a comparison with the results obtained from CASSCF (10,10) calculations (Table S4). From Table S4, we found that the trend given by the CASSCF method is consistent with our calculations under UM06-2X/6-311++G (d, p), which confirms the accuracy of the present work.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies suggest that singlet and triplet states are close in energy in TTFtt dicationic complexes. , Consistent with this hypothesis, the 1 H NMR spectra of 1 , 2 , and 3 appear diamagnetic; however, there is a significant magnetic moment detected via Evans method measurements for all three complexes (see the Supporting Information). Furthermore, a strong signal at g = 2 suggestive of an organic radical is present in the electron paramagnetic resonance (EPR) spectra of these complexes (see the Supporting Information).…”
Section: Resultssupporting
confidence: 76%
“…[40][41] Moreover, we have recently reported a set of bimetallic complexes featuring tetrathiafulvalene tetrathiolate (TTFtt) as a bridging ligand which exhibit redox-activity, intense near-infrared absorption and emission, and air/water stability. [42][43] Most importantly, transition metal complexes of TTFtt support a formal TTF 2+ oxidation state. This oxidation state exhibits a small ground-state singlet-triplet gap which could be optically excited and thus in principle act as an optically addressable electron spin qubit like an NVcenter.…”
Section: The Bigger Picturementioning
confidence: 99%
“…We have previously reported experimental and theoretical data on PtTTFtt that support a unique diradicaloid electronic structure. [42][43] Variational two-electron reduced density matrix (V2RDM) calculations predict a singlet ground state with a small singlet-triplet gap giving rise to a thermally accessible triplet excited state. [43][44][45][46][47] These calculations also predict that nearly all the ground and excited state spin density is centered on the central TTFtt core with slight diffusion to Pt (Figure 1B).…”
Section: Ptttftt Electronic Structurementioning
confidence: 99%
See 1 more Smart Citation